Not working at work: Loafing, unemployment and labor productivity - Michael C. Burda; Katie Genadek; Daniel S. Hamermesh (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2015)
Using the American Time Use Survey (ATUS) 2003-12, we estimate time spent by workers in non-work while on the job. Non-work time is substantial and varies positively with the local unemployment rate. While the average time spent by workers in non-work conditional on any positive non-work rises with the unemployment rate, the fraction of workers who report time in non-work varies pro-cyclically, declining in recessions. These results are consistent with a model in which heterogeneous workers are paid efficiency wages to refrain from loafing on the job. That model correctly predicts relationships of the incidence and conditional amounts of non-work with wage rates and measures of unemployment benefits in state data linked to the ATUS, and it is consistent with observed occupational differences in non-work.
Keywords: J22; E24; 330; time use; non-work; loafing; shirking; efficiency wage; labor productivity